Cerebellar Theta Burst Stimulation on Walking Function in Stroke Patients: A Randomized Clinical Trial - Xie, Yun-Juan; Wei, Qing-Chuan; Chen, Yi; Liao, Ling-Yi; Li, Bao-Jin; Tan, Hui-Xin; Jiang, Han-Hong; Guo, Qi-Fan; Gao, Qiang (Frontiers in Neuroscience, 2021)
Objectives The objective of this study was to explore the efficacy of cerebellar intermittent theta burst stimulation (iTBS) on the walking function of stroke patients. Methods Stroke patients with walking dysfunction aged 25-80 years who had suffered their first unilateral stroke were included. Participants were randomly assigned to either the intervention group, receiving cerebellar iTBS, or the control group. The primary outcome measure was Fugl-Meyer Assessment - Lower Extremity scores. Secondary outcomes included walking performance and corticospinal excitability. The Assessment was performed before the intervention (T0), after one-week intervention (T1) and two-week intervention (T2). Results A total of 36 patients (mean [SD] age, 53 [7.93] years; 10 women [28%]) were enrolled in the study. The analysis for Fugl-Meyer Assessment for lower extremity revealed a significant effect of time compared to baseline (F = 31.1172, P < 0.0001), there was no significant interaction between time and group (F = 0.1782, P = 0.7255,ε= 0.612). Repeated-measures mixed ANOVA showed that there was significant interaction between time and group in comfortable walking time (F = 6.5242, P = 0.0080,ε= 0.680), between-group comparisons revealed significant differences at T1 (P = 0.0072) and T2 (P = 0.0133). The statistical analysis of maximum walking time showed that there was significant interaction between time and groups (F = 5.4354, P = 0.0115,ε= 0.791). Compared with T0, the differences of maximum walking time between the two groups at T1 (P = 0.0227) and T2 (P = 0.0127) were statistically significant. However, both the Timed up and go test and functional ambulation category scale did not yield significant differences between groups (P > 0.05). Conclusion Our results revealed that applying iTBS over the contralesional cerebellum paired with physical therapy could improve walking performance in patients after stroke, implying that cerebellar iTBS intervention may be a noninvasive strategy to promote walking function in these patients. This study was registered at ChiCTR, number ChiCTR1900026450.